QUANTITATIVE AND QUALITATIVE VARIABILITY OF EPIPHYTIC ALGAE ON THREE AQUATIC PLANTS IN EUPHRATES RIVER, IRAQ - Hassan, F. M.; SALAH, M. M. SALAH; SALMAN, J. M. (Iraqi Journal of Aquaculture, 2022)
The epiphytic algae were studied on three aquatic plants (Ceratophyllum demersum, Myriophyllum verticillatum and Potamogeton pectinatus) from seven stations in Euphrates River between Hindia barrage and Al-Kufa city-Iraq, during summer 2004 and spring 2005. A total of (97) species were identified, diatoms were dominant in their species number (73% from the total number), followed by chlorophyta, then cyanophyta and Euglenophyta. Variations were recorded in the species number among the host macrophyte, as well as, among different seasons for each plant. The biomass of epiphytic algae varied among the plant host, diatoms species were dominated and several genera have large number of species as Cymbella, Gomphonema, Nitzschia and Synedra. Most studied stations showed high population density.